Bee foraging preferences on three willow (Salix) species: Effects of species, plant sex, sampling day and time of day. (11th October 2020) - Mosseler, Alex; Major, John; Ostaff, Don; Ascher, John
Abstract: Our objective was to examine how bee foraging preferences on dioecious willows are influenced by plant sex, time of day, by sampling date on multiple sites and across different willow species. In a common garden experiment examining diurnal pollinator visitation patterns of Andrena bees (andrenids), there was a strong preference for male willow plants: 87% of visitations on male plants of Salix eriocephala (ERI) and 71% on males of S. interior (INT). The significant plant sex × time of day interaction was not a result of a change in bee preference for a certain plant sex during a certain part of the day but rather the result of diurnal changes in the magnitude of the preference of andrenid bees for male willow plants. Visits to male flower catkins were highest in the morning and early afternoon, peaking at midday. Visits to female catkins showed a more uniform, lower frequency visitation pattern throughout the day. In a larger field test at a reclaimed former coal mine site, which included S. cordata (COR) as well as ERI and INT, there were no sampling date × plant sex or sampling date × plant sex × willow species interactions. This indicates no plant sex switching behaviour by sampling date for the three willow species. Preference for male plants was greatest on the first sampling day and the proportion of male preference continued to decline until the fourth and final sampling day. On the mine site, 17 of the 25 Apoidea bee species identified were andrenids, and they represented 92% of the 744 individual bees collected while foraging on willow catkins. In addition, the overall number of observed and collected Apoidea bees visiting available flowering willow plants showed that the preference for male plants was 83%, 72% and 91%, for ERI, INT and COR, respectively. We discuss possibilities for promoting populations of native bees to increase commercial fruit and berry crop pollination by using willows as natural sources of pollen and nectar, thereby reducing costs of production associated with the annual importation of commercial bees. Abstract : In both a common garden experiment and within artificially established populations of three willow species on a former coal mine site in eastern Canada, we observed a strong foraging preference by Andrena bees on male willow plants. We discuss possibilities for promoting populations of native bees to increase commercial fruit and berry crop pollination by using willows as natural sources of pollen and nectar, thereby reducing costs of production associated with the annual importation of commercial bees.